PENGARUH GAYA BELAJAR DAN STRATEGI PEMBELAJARAN TERHADAP HASIL BELAJAR AL-QUR’AN MAHASISWA UIN MAULANA MALIK IBRAHIM MALANG - Thoifah, I’anatut (J-PAI: Jurnal Pendidikan Agama Islam, 2018)
This study aims to investigate the interaction of learning style and learning strategies towards the result of learning Al Qur’an among freshmen of Ma’had al-Jami’ah UIN Maulana Malik Ibrahim Malang. A quantitative method with 2x2 factorial design was used in this study. The samples of this study were 40 students of UIN Maulana Malik Ibrahim Malang who were selected by using random purposive technique sampling. They were classified into two groups; experimental and control groups. In the process of analysis, the students’ score of learning Quran in terms of tajwid were correlated with the grouped students based on their learning style and learning strategies. The result of this study showed that there was a different result of learning Quran between the students with field independent learning style and field dependent learning style. Besides, there was also a different result of learning Quran between the students with musical and conventional learning strategy. However, there was no interaction between learning style and learning strategies towards the students’ result of learning Qur’an.Keywords: learning styles, learning strategies, and the results of the Study